The social image of food: Associations between popularity and eating behavior. (1st July 2017) - König, Laura M.; Giese, Helge; Stok, F. Marijn; Renner, Britta
Abstract: One factor that determines what we eat and why we eat is our social environment. In the present research, two online studies examined the relationship between food intake and social images. Specifically, the present research assessed the relationship between the food intake university students ascribed to peers who varied in popularity and own self-reported food intake, and whether this relationship was moderated by identification with the peer group. Participants ( N  = 97 in Study 1; N  = 402 in Study 2) were randomly presented with one of four (Study 1) or two of eight (Study 2) vignettes describing a popular or unpopular student (male or female) from their university without receiving any information about the peer's eating behavior. Subsequently, healthy and unhealthy eating ascribed to the peers and own self-reported eating behavior were assessed. Results indicated that popular peers were perceived to eat more healthily than unpopular peers. Moreover, eating behavior ascribed to popular peers were associated with own healthy and unhealthy eating. Importantly, the relationship between healthy eating behavior ascribed to popular peers and own healthy eating behavior was moderated by identification with the student group – the more participants identified with their peers, the more their own eating was aligned with the healthy eating ascribed to a popular peer. Hence, the popularity of others seems to shape perceptions of the food they eat and may facilitate healthy eating via social influence.